Comparison of the Dyspnoea-12 and Multidimensional Dyspnoea Profile in people with COPD. Issue 3 (2nd March 2017) - Williams, Marie T.; John, David; Frith, Peter
We directly compared convergent, discriminant and concurrent validity of the Dyspnoea-12 (D-12) and Multidimensional Dyspnoea Profile (MDP) in people with chronic obstructive pulmonary disease. Breathlessness measures (D-12, MDP, visual analogue scales and descriptors) were completed for two focal periods (daily life and end of walk test). Instrument structure (D-12 and MDP item grouping) was assessed with factor analysis. Differences between airflow severity stage and focal periods (ANOVA, t-test and Chi-squared test), associations between D-12 and MDP (r, r 2 for static pulmonary function, 6-min walk test and self-reported measures of impairment) and individual consistency for comparable items of the D-12 and MDP (McNemar's test) were assessed. In 84 participants (mean±sd age 70±9 years, 47 males, forced expiratory volume in 1 s 48±17% predicted), item groupings were confirmed for both focal periods. Developer-recommended single and subdomain scores were highly correlated, and demonstrated similar convergent, discriminant and concurrent validity. Individual consistency differed between the D-12 and MDP according to item/item groups. At the level of developer-recommended single and subdomain scores, the D-12 and MDP share similar psychometric properties, but these instruments serve different purposes, do not assess the same sensations or emotions and are not interchangeable. The D-12 and MDP share similar psychometric properties but serve different purposes and are not interchangeable http://ow.ly/VXmX305OkdN